2009
DOI: 10.1007/s10709-008-9345-8
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypic and molecular polymorphisms in Ctenomys torquatus (Rodentia: Ctenomyidae): taxonomic considerations

Abstract: The rodent genus Ctenomys (tuco-tucos) comprises more than 60 described species, and shows extraordinary inter- and intraspecific karyotypic variation. The most widely distributed species of Ctenomys in Brazil is C. torquatus. Although several cytogenetic studies have been done, the karyotypic variability of this species is still poorly known. In this paper we report two new diploid numbers for C. torquatus: 2n = 40 and 2n = 42, both showing AN = 72. The new distribution limits of C. torquatus here reported in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…Although the members of this species group from Corrientes are closely related to C. torquatus with respect to karyotype morphology, they are phylogenetically distant ( Fig. 6B; Fernandes et al 2009b;Giménez et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the members of this species group from Corrientes are closely related to C. torquatus with respect to karyotype morphology, they are phylogenetically distant ( Fig. 6B; Fernandes et al 2009b;Giménez et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The percent of variance explained for each axis is given in parentheses. from 2n ¼ 40 to 46, with a metacentric 1st pair and Robertsonian rearrangements thought to be responsible for the variation in chromosome numbers (Fernandes et al 2009b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of seven populations have been studied up to now in the proximities to the Iberá wetland: four located at the western margins of the wetland, two in the east and one isolated on a sandy elevation surrounded by waterlogged lowlands located in the center of the wetland (Figure 2). In mtDNA studies (Fernandes et al 2009, Caraballo et al 2012) their membership to the Corrientes group was confirmed rejecting its affinity to C. torquatus. With the exception of Curuzú Laurel, which falls apart probably due to incomplete lineage sorting, all the Iberanan populations form a monophyletic group (Caraballo et al 2012(Caraballo et al , 2016.…”
Section: Iberá I Iberá Ii and Iberá Iiimentioning
confidence: 94%